Evaluation of 24-segment sphericity index of fetal heart using FetalHQ. (2nd December 2022) - Hata, Toshiyuki; Koyanagi, Aya; Yamanishi, Tomomi; Bouno, Saori; Takayoshi, Riko; AboEllail, Mohamed Ahmed Mostafa; Miyake, Takahito
Abstract: Objective: To evaluate the 24-segment sphericity index (SI) of the fetal heart using Fetal HQ regarding the change with advancing gestation and reproducibility. Methods: Eighty-one pregnant women at 18–21 + 6 and 28–31 + 6 weeks were studied using Fetal HQ to calculate 24-segment SI of left and right ventricles. Intra- and inter-class correlation coefficients and intra- and inter-observer agreements of measurements for SI were assessed in each segment. Results: With respect to intra-observer reproducibility, all SI values showed correlations between 0.596 and 0.774 for the left ventricle, and between 0.491 and 0.764 for the right ventricle, with good intra-observer agreements except for right ventricular segment 11–15. With respect to inter-observer reproducibility, all SI values showed correlations between 0.473 and 0.755 for the left ventricle, and between 0.48 and 0.767 for the right ventricular segment 1–18. However, right ventricular segment 19–24 showed no correlations. Good inter-observer agreements were noted in the right ventricle, whereas poor inter-observer agreements were evident in the left ventricle. There were significant differences in the mean SI values in the apical segment of the left ventricle between 18–21 + 6 and 28–31 + 6 weeks ( p  < .05), whereas there were no significant differences in the mean SI values in the right ventricle between both gestational ages. Conclusion: These results show that measurements of 24-segment SI of fetal heart had relatively low reliability of measurements performed by experienced sonographers. This may suggest that more training on proper placement of the 3 end-systolic and end-diastolic reference points during the initial analysis may be relevant.